Mesentric vein thrombosis-bowel gangrene: a case series - Kumar, Sampath; V., Vijayalakshmi; Jayasankar, Nivetha; Ross, Kannan (International Surgery Journal, 2022)
Mesenteric vein thrombosis is a condition often misdiagnosed due to its vague and misleading clinical presentation which can cause intestinal angina, infarct, peritonitis. In patients with no peritonitis or evidence of gangrene, they can be managed conservatively with anti-coagulants. In this case series we discuss about various methods of presentation of patients with mesenteric vein thrombosis admitted in Rajiv Gandhi government general hospital during a time frame of June 2020 to April 2022 under institute of general surgery and management followed for different patients.